Phosphatidylinositol 4-kinase is a viable target for the radical cure of Babesia microti infection in immunocompromised hosts - Ji, Shengwei; Galon, Eloiza May; Amer, Moaz M.; Zafar, Iqra; Yanagawa, Masashi; Asada, Masahito; Zhou, Jinlin; Liu, Mingming; Xuan, Xuenan (Frontiers in Cellular and Infection Microbiology, 2022)
Human babesiosis is a global emerging tick-borne disease caused by infection with intra-erythrocytic parasites of the genus Babesia. With the rise in human babesiosis cases, the discovery and development of new anti-Babesia drugs is essential. Phosphatidylinositol 4-kinase (PI4K) is a widely present eukaryotic enzyme that phosphorylates lipids to regulate intracellular signaling and trafficking. Previously, we have shown that MMV390048, an inhibitor of PI4K, showed potent inhibition against Babesia species, revealing PI4K as a druggable target for babesiosis. However, twice 7-day regimens failed to clear Babesia microti parasites from the immunocompromised host. Hence, in this study, we wanted to clarify whether targeting PI4K has the potential for radical cure of babesiosis. In a B. microti-infected SCID mouse model, a 64-day-consecutive treatment with MMV390048 resulted in clearance of parasites. Meanwhile, an atovaquone (ATO) resistant parasite line was isolated from the group treated with ATO plus azithromycin. A nonsynonymous variant in the Y272C of the cytochrome b gene was confirmed by sequencing. Likewise, MMV390048 showed potent inhibition against ATO-resistant parasites. These results provide evidence on PI4K as a viable drug target for the radical cure of babesiosis, which will contribute in designing new compounds that eradicate parasites.